Analisis Keselamatan dan Kesehatan Kerja (K3) pada Pemeliharaan Kubikel 20 kV di Gardu Distribusi PLN - Alifah, Nur; Bagus Dwi Cahyono (Jurnal Kendali Teknik dan Sains, 2023)
Occupational Safety and Health  (OHS) is a crucial aspect in energy infrastructure maintenance operations, such as Distribution Substations (GD) owned by PLN. Cubicle maintenance work at GD PLN is a critical activity that involves high risks to worker safety and health and has an impact on the continuity of electricity supply.   This study aims to analyze the application of K3 to 20 kV  cubicle maintenance work at GD PLN. Through a qualitative approach, data are obtained based on observation, interviews and  literature studies. The results showed that the application of K3 was obtained through  safety briefing activities  and  K3 documentation which included SOPs, inspectors, HIRARC and JSA. While the maintenance process  of  the 20 kV  cubicle includes preparation, implementation and completion.